Molecular characterization and expression analysis of the remorin genes in tomato (Solanum lycopersicum L.) - Li, Hui; Wang, Xiao; Zhuo, Yue; Chen, Shuisen; Lin, Jingwei; Ma, Hui; Zhong, Ming (Frontiers in Plant Science, 2023)
Remorin (REMs) are plant-specific and plasma membrane-associated proteins that play an essential role in the growth and development of plants and adaptations to adverse environments. To our knowledge, a genome-scale investigation of the REM genes in tomato has never been systematically studied. In this study, a total of 17 SlREM genes were identified in the tomato genome using bioinformatics methods. Our results demonstrated that the 17 members of SlREM were classified into 6 groups based on phylogenetic analysis and unevenly distributed on the eight chromosomes of tomato. There were 15 REM homologous gene pairs between tomato and Arabidopsis. The SlREM gene structures and motif compositions were similar. Promoter sequence analysis showed that the SlREM gene promoters contained some tissue-specific, hormones and stress-related cis-regulatory elements. Expression analysis based on qRT-PCR (Real-time quantitative PCR) analysis showed that SlREM family genes were were differentially expressed in different tissues, and they responded to ABA, MeJA, SA, low-temperature, drought and NaCl treatments. These results potentially provide relevant information for further research on the biological functions of SlREM family genes.